Factors Influencing the financial performance of GLCs in Malaysia and Singapore / Musliha Musman, Salwa Muda and Raziah Bi Mohamed Sadique - Musman, Musliha; Muda, Salwa; Mohamed Sadique, Raziah Bi (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2024)
Government-Linked Companies (GLCs) are enterprises in which the government holds a significant ownership stake, either directly or indirectly. Direct ownership occurs when government entities, such as the Ministry of Finance or specific agencies, own shares in a company. In contrast, indirect ownership happens when the government holds shares through entities like sovereign wealth funds or state-owned corporations, which then invest in other companies. GLCs play a crucial role in various countries around the world. For instance, Malaysia is renowned for its extensive network of GLCs, which are integral to its economic framework, featuring key players such as Petronas, Khazanah Nasional, and Telekom Malaysia. In Singapore, GLCs, often referred to as State-Owned Enterprises (SOEs), include influential companies like Singapore Airlines and Temasek Holdings, which have a significant impact both locally and internationally.